RESPON TANAMAN TOMAT (Lycopersicum esculentum Mill.) PADA BEBERAPA KOMPOSISI MEDIA TANAM YANG DIBUDIDAYAKAN DENGAN SISTEM VERTIKULTUR - Desta Monika Saragih; Syafrinal Syafrinal; Murniati Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the composition of the best growing media for the growth and yield of tomato plants withverticultural systems. This research was carried out in the greenhouse of the University of Riau Faculty of Agriculture Experiment station for 4 months starting from October 2017 to January 2018.This study was an experiment using a randomized block design (RBD)consisting of 5 treatments, namelyP1 = Soil Inceptisol + Sand + Compost TKKS (1 : 1 : 1), P2 = Soil Inceptisol + Sand + Compost TKKS (1 : 1 : 2), P3 = Soil Inceptisol + Sand + Compost TKKS(1 : 2 : 1), P4 = Soil Inceptisol + Sand + Compost TKKS (2 : 1 : 1) and P5 = Soil Inceptisol + Sand + Compost TKKS (2 : 2 : 1).The parameters observed were plant height, stem diameter, age of first flowers appearance, age of first harvest, number of flowers, number of fruits and weight of fruit. The 2 : 1 : 1 Planting media composition cultivated with verticulture system produces fruit weight an average of 286,4 g in tomato plants which tend to be better. Keywords: Tomato plants, composition of planting media, cultivation of verticulture systems.